Successful use of telemedicine for evaluation of infantile hemangiomas during the early COVID‐19 pandemic: A cross‐sectional study. Issue 5 (22nd June 2022) - Kittler, Nicole W.; Frieden, Ilona J.; Abuabara, Katrina; Siegel, Dawn H.; Horii, Kimberly A.; Mathes, Erin F.; Blei, Francine; Haggstrom, Anita N.; Streicher, Jenna L.; Metry, Denise W.; Garzon, Maria C.; Morel, Kimberly D.; et al.
Abstract: Background/Objectives: The COVID‐19 pandemic prompted a rapid expansion in the use of telemedicine. This study aimed to assess the experiences of hemangioma specialists utilizing telemedicine during the COVID‐19 pandemic to evaluate and manage infantile hemangiomas (IH), including perceived effectiveness of different modalities and barriers to care delivery. Methods: Multicenter cross‐sectional study asking providers to describe their experiences using telemedicine for initial evaluation of IH from March to September 2020. Results: The study included 281 patients from 15 medical centers internationally. Median time from referral to evaluation was 17 days. Median physician confidence in performing evaluations via telemedicine was 95.0 (IQR 90.0–100.0). Most evaluations were performed via video communication with photographs or audio communication with photographs; when not initially available, photographs were requested in 51.4%. Providers preferred follow‐up modalities that included photographs. Conclusions: Physicians with extensive expertise in managing IH are confident in their abilities to assess and manage IH via telemedicine including initiating treatment in patients without risk factors for beta‐blocker therapy. There was a preference for hybrid modalities that included photographs. The data suggest that telemedicine can be effective for managing IH and may decrease wait times and improve specialist reach to underserved areas.